DIFFICULTIES IN LEARNING ENGLISH AT THE FIRST SEMESTER STUDENTS OF ISLAMIC EDUCATION STUDY PROGRAM OF STATE ISLAMIC UNIVERSITY OF DATOKARAMA PALU - Afifah Afifah; Suleman Suleman (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The objective of this research is to find out the difficulties in learning English at the first semester students of Islamic Education Study Program of State Islamic University of Datokarama Palu. This is a qualitative research applying an interview as the instrument. The research question is “What are the difficulties in learning English at the first semester students of Islamic Education Study Program of State Islamic University of Datokarama Palu?” The respondents are twenty six first semester students of Islamic Education Study Program of State Islamic University of Datokarama Palu. Through the interview, the researchers discovered four difficulties the respondents shared related to learning English. The first is pronunciation. They find it hard to guess the pronunciation of some English words that they read as well as to pronounce the words correctly. The second one is the writing of English. Even if they already know the pronunciation, they still find it troublesome to write English since the writing is different from the pronunciation. The next difficulty is the grammar. Although the materials of English at schools have included many parts of grammar, they still find it tough to construct grammatical correct sentences when they already become university students. The last thing that becomes their difficulty is limited vocabulary that leads them to the problem in developing productive skill such as constructing sentences and receptive skill such as listening to English conversation